The contingent effects of supervisor positive gossip on employee receivers: the moderating role of performance goal orientation - Fangliang Zhang; Chunling Zhu (Frontiers in Psychology)
While research on supervisor gossip has sought to provide a balanced examination of its potential benefits and drawbacks for employees, there remains a significant disparity in the attention given to positive versus negative gossip. By integrating social comparison theory and goal orientation theory, we propose that the impact of supervisor positive gossip on employee receivers’ self-efficacy and job performance is contingent upon the level of employees’ performance goal orientation (PGO). We argue that high-PGO employees are expected to experience lower levels of self-efficacy upon receiving supervisor positive gossip, whereas low-PGO employees are anticipated to experience higher self-efficacy. Additionally, we suggest that employees’ self-efficacy mediates the relationship between supervisor positive gossip and job performance. Dyadic data collected from 161 supervisors and 556 employees in a Chinese company support our hypotheses. Our findings contribute to a more nuanced discourse on the role of supervisor positive gossip in organizational dynamics and its implications for employee well-being and productivity.